Central HER2 IHC and FISH analysis in a trastuzumab (Herceptin) phase II monotherapy study: assessment of test sensitivity and impact of chromosome 17 polysomy. Issue 1 (5th April 2007) - Hofmann, M; Stoss, O; Gaiser, T; Kneitz, H; Heinmöller, P; Gutjahr, T; Kaufmann, M; Henkel, T; Rüschoff, J
Abstract : Aims: To investigate the correlation between centrally assessed human epidermal growth factor receptor 2 (HER2) immunohistochemistry (IHC) and fluorescence in situ hybridisation (FISH) results and response to treatment of patients with metastatic breast cancer enrolled in a first-line, phase II, open-label, 3-weekly trastuzumab (Herceptin) monotherapy trial (WO16229). Methods: Samples from participants in the WO16229 trial were collected and tumour HER2 status determined by IHC and FISH. HER2 test results were interpreted according to manufacturers' test kit protocols. Responders were defined as patients showing either partial or complete responses. Results: Response data were available for 103/105 patients; centrally confirmed HER2 status was available for 95 patients. Intra-laboratory concordance for central IHC and FISH results was 93%. Complete responses were seen in two patients; their samples were IHC 3+ and FISH positive. Partial responses were seen in 17 patients; all were IHC 3+ and 14 were FISH positive. IHC and FISH showed 100% and 84.2% sensitivity, respectively, in determining response to trastuzumab. Polysomy was observed in 27% of patients; six responded to trastuzumab treatment. All six responders showed HER2 overexpression (IHC 3+) and HER2 gene amplification; two were FISH negative due to chromosome 17 polysomy. Conclusions: HER2 determination by IHC and FISH correlates with clinical response data in the WO16229 trial with high concordance of IHC and FISH results. Polysomy is the major cause of response in FISH-negative cases; polysomic cases should be retested by strictly standardised IHC.